Dysrhythmia, dysphoria, and depression: the interaction of learned helplessness and circadian dysrhythmia in the pathogenesis of depression. - Healy, D; Williams, J (1988)
Increasing evidence suggests that endogenomorphic depressions involve a disruption of circadian rhythms. We review this evidence in relation to comparable findings in animal helplessness studies. We examine the neurophysiological, neuropsychological, and nosological implications of such findings for both helplessness and depression. A disruption of circadian rhythms provides a framework, which suggests three sets of possible interactions between psychology and biology in the pathogenesis of helplessness and endogenomorphic depressions. First, it offers a mechanism to account for the role of life events in the precipitation of such depressions. Second, it provides a potent stimulus to the generation of the misattributions typical of depression and helplessness. Third, it provides a stress to which certain personalities may be particularly vulnerable. We discuss the theoretical, research, and remedial implications of these interactions.